Arthroscopic Subscapularis Tendon Repair Using the Mason-Allen Technique - Huang, Junqi; Cheng, Jiajia; Tang, Shitian; Shi, Bo; Liu, Gang; Xie, Gangtai (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Background Arthroscopic rotator cuff repair has recently been popularized for treating tears. In a biomechanical trial, the Mason-Allen stitch improved the fixation quality of poorly vascularized tendons. The use of this technique involving the subscapularis tendon remains rare. The aim of this study was to evaluate the clinical outcomes of Mason-Allen technique repaired subscapularis tendons.Methods A retrospective research of collected data from 98 patients with subscapularis tears who had undergone arthroscopic repair between May 2015 and December 2018. There were 75 males and 23 females. The mean age was 56.4 ± 9.6 years and the mean follow-up was 12.5 ± 4.0 months. The visual analog scale (VAS), American Shoulder and Elbow Surgeons (ASES) score, and Constant-Murley score were used to analyze shoulder function. An MRI was performed to assess the integrity of the repair.Results Patients had significantly less pain and a better active range of motion compared with preoperative levels. VAS improved significantly from a preoperative mean of 3.42 to a postoperative mean of 1.91. ASES increased significantly from the preoperative mean of 43.6 to the postoperative mean of 74.5. Seven cases suffered from retears, which were confirmed by an MRI examination.Conclusion Arthroscopic rotator cuff repair with the Mason-Allen method resulted in a decreased level of pain and satisfied function recovery.
Keywords: rotator cuff tear; subscapularis tendon; arthroscope; Mason-Allen technique